2015
DOI: 10.1016/j.ebiom.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

CRF19_cpx is an Evolutionary fit HIV-1 Variant Strongly Associated With Rapid Progression to AIDS in Cuba

Abstract: BackgroundClinicians reported an increasing trend of rapid progression (RP) (AIDS within 3 years of infection) in Cuba.MethodsRecently infected patients were prospectively sampled, 52 RP at AIDS diagnosis (AIDS-RP) and 21 without AIDS in the same time frame (non-AIDS). 22 patients were sampled at AIDS diagnosis (chronic-AIDS) retrospectively assessed as > 3 years infected. Clinical, demographic, virological, epidemiological and immunological data were collected. Pol and env sequences were used for subtyping, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 58 publications
6
49
2
2
Order By: Relevance
“…In addition to the epidemiological impact, the spread of HIV-1 subtypes is clinically relevant: HIV-1 clades show differences in pathogenesis and resistance pathways, with implications for clinical outcomes, diagnosis, viral quantification, and vaccine development (14)(15)(16)(17)(18)(19). With continuous discovery of new HIV-1 strains (https://www.hiv.lanl .gov/content/sequence/HIV/CRFs/CRFs.html) coupled with the increasing phylogeography and phylodynamics of non-B subtypes spreading into Western countries (6-8; see also WHO data at http://www.who.int/gho/hiv/en/), it would be of paramount importance to accurately identify newly emerging strains, both for efficient molecular epidemiological surveillance and for optimal clinical management of patients infected with diverse HIV-1 strains, particularly in Italy, where the migration rate is high (12,13).…”
mentioning
confidence: 99%
“…In addition to the epidemiological impact, the spread of HIV-1 subtypes is clinically relevant: HIV-1 clades show differences in pathogenesis and resistance pathways, with implications for clinical outcomes, diagnosis, viral quantification, and vaccine development (14)(15)(16)(17)(18)(19). With continuous discovery of new HIV-1 strains (https://www.hiv.lanl .gov/content/sequence/HIV/CRFs/CRFs.html) coupled with the increasing phylogeography and phylodynamics of non-B subtypes spreading into Western countries (6-8; see also WHO data at http://www.who.int/gho/hiv/en/), it would be of paramount importance to accurately identify newly emerging strains, both for efficient molecular epidemiological surveillance and for optimal clinical management of patients infected with diverse HIV-1 strains, particularly in Italy, where the migration rate is high (12,13).…”
mentioning
confidence: 99%
“…However, a recent report from our group found that CRF19_cpx was associated with rapid progression to AIDS and one of the hypotheses for explaining this rapid progression was the finding of higher levels of RANTES and significantly more frequent proportion of X4 virus among the patients infected with this viral variant [20].…”
Section: Discussionmentioning
confidence: 91%
“…A false-positive rate (FPR) <5% are mainly X4 and ≥ 20% are mainly R5 variants. Therefore, we classified V3 loop sequences with FPR ≥ 20% as R5 viruses, with FPR ≥ 5% and <20% as dual-tropic viruses (R5X4) and with FPR <5% as X4 viruses as described previously [20,28,29].…”
Section: Viral Tropism and Co-receptor Usementioning
confidence: 99%
See 1 more Smart Citation
“…29 . Recientemente se describió una forma recombinante con rápida progresión a SIDA, como es el caso del CRF19_cpx, presente en la epidemia cubana 30,31 . Las diferencias encontradas en el presente estudio dado lo pequeña y variado de la muestra no se establecieron de forma significativa.…”
Section: Subtiposunclassified